PENGELOLAAN DANA DESA DALAM PENANGANAN COVID-19 DI DESA PULAU KOMANG SENTAJO KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Afrila Wahyu Ningsih; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Covid-19 outbreak entered Indonesia in March 2020 and Pulau Komang Sentajo Village was also affected by the Covid-19 pandemic. Various efforts have been made by the government for the prevention and handling of Covid-19, including the Covid-19 Response Village policy and Direct Cash Assistance (BLT-Dana Desa) sourced from village funds. However, in its management, the village government of Pulau Komang Sentajo often occurs delays in making accountability reports and the beneficiaries of the BLT-Village Fund have not been on target. The purpose of this study was to identify and analyze the management of village funds and to find out the inhibiting factors for managing village funds in handling Covid-19 in Pulau Komang Sentajo Village, Sentajo Raya District, Kuantan Singingi Regency. This study used a purposive sampling technique with qualitative research using descriptive analysis. The collection of data obtained, both primary data and secondary data were collected through interviews, observations and documentation and then analyzed based on research problems. The results of this study indicate that the management of village funds in handling Covid-19 in Pulau Komang Sentajo Village, Sentajo Raya District, Kuantan Singingi Regency there are still obstacles, this is caused by several inhibiting factors, namely the lack of human resource capabilities, and lack of community participation of Pulau Komang Sentajo Village.  Keyword: Management, Village Fund, Covid-19, Pulau Komang Sentajo Village